Análisis presupuestario de los gastos del Gobierno Autónomo Descentralizado Parroquial Rural de Febres Cordero en el período 2023. - Almeida Ayala, Jeniffer Stephania (2024)
The budget is an essential tool in public organizations. Through this instrument it is possible to project the income and expenses they will have during a specific period and thus distribute financial resources appropriately to meet the objectives and satisfy the needs of the population. . The objective of the research is: Analyze the expenditure budget by observing the budget statements of the Rural Parochial Decentralized Autonomous Government of Febres Cordero in the period 2023. The study was made up of a mixed approach and descriptive scope. The types of research applied were two: documentary and field, the methods used are: inductive, deductive and synthetic analytical. On the other hand, the techniques applied to collect information were: an interview with the financial director to learn about aspects related to budget management and an analysis of the expense budget schedules. For this, the instrument was applied: a registration form and an interview guide with 5 semi-structured questions. It is concluded that the management carried out in the Rural GADP of Febres Cordero is not effective and has many weaknesses that urgently need to be improved, since it is necessary to considerably reduce the gap between what was planned and what was executed, in order to obtain satisfactory results.